Equilibrium mergers in a composite good industry with efficiencies - Cristina Pardo-Garcia; Jose J. Sempere-Monerris (SERIEs - Journal of the Spanish Economic Association, 2015)
This paper studies equilibrium merging behavior in composite good industries. Component producers face the option to either merge with a similar component producer (horizontal merger) or a complementary one (vertical merger) of a composite good. Focusing only on strategic reasons, vertical mergers arise at equilibrium only when composite goods are very differentiated or when the number of producers is large while horizontal mergers arise otherwise. When efficiencies are considered, higher marginal cost savings are required for a horizontal merger in a composite industry not to result in a price increase as compared with those required for a regular industry. This finding can be used by antitrust authorities to be more demanding when dealing with horizontal mergers in composite goods industries.
Keywords: L13; L41; 330; Composite goods; Substitutes; Complements; Horizontal merger; Vertical merger; Efficiency effects; Diversion ratio